Precision nitrogen management practices in wheat influences nutrient uptake and their use efficiencies and fertility status of soil under conservation agriculture
A field experiment was conducted at New Delhi during Rabi season of 2012-13 to study the precision nitrogen management in wheat grown under conservation agriculture. The experiment was laid out in a factorial randomized block design with twenty treatment combinations four nutrient management in preceding maize [absolute control, recommended dose of fertilizers (RDF), 50% RDF and site-specific nutrient management (SSNM)] and five precision N management practices in wheat [control, RDF, green seeker, SPAD and soil-test crop response (STCR)